2022
DOI: 10.1007/s10815-022-02517-w
|View full text |Cite
|
Sign up to set email alerts
|

The impact of past COVID-19 infection on pregnancy rates in frozen embryo transfer cycles

Abstract: Purpose To study the effect of SARS-CoV-2 infection on pregnancy rates in frozen embryo transfer (FET) cycles. Methods A retrospective cohort study including women under the age of 42 with documented SARS-CoV-2 infection up to 1 year prior to treatment, undergoing FET cycles in the first half of 2021, with transfer of embryos generated prior to the infection. Controls were SARS-CoV-2 non-diagnosed, non-vaccinated women matched by age, number, and day of embryo transfer.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 22 publications
(5 reference statements)
1
19
1
Order By: Relevance
“…The outcomes of the first fresh ART cycle in 121 patients with previous COVID-19 (within 12 months from diagnosis) were retrospectively compared with 121 patients that did not have COVID-19 previously ( Youngster et al , 2022a ). From this largest study to date, recent past SARS-CoV-2 infection was found to have no impact on oocyte yield, maturation rate, fertilization rate, number of vitrified embryos and clinical pregnancy rates.…”
Section: Resultsmentioning
confidence: 99%
“…The outcomes of the first fresh ART cycle in 121 patients with previous COVID-19 (within 12 months from diagnosis) were retrospectively compared with 121 patients that did not have COVID-19 previously ( Youngster et al , 2022a ). From this largest study to date, recent past SARS-CoV-2 infection was found to have no impact on oocyte yield, maturation rate, fertilization rate, number of vitrified embryos and clinical pregnancy rates.…”
Section: Resultsmentioning
confidence: 99%
“…In China, the control of COVID-19 has been relaxed since December 2022, and the number of couples infected with SARS-CoV-2 during assisted reproductive technology (ART) treatment increased sharply during that period. Angiotensin-converting enzyme 2 (ACE2) and transmembrane protease serine subtype 2 (TMPRSS2) are expressed in the reproduction system in both males and females 1 ; therefore, reproductive function is theoretically vulnerable to SARS-CoV-2 infection, and many studies 2,3 have explored the possible effect of SARS-CoV-2 infection on the human reproductive system. A recent review 4 summarized published data and clarified the effect of SARS-CoV-2 and COVID-19 on human fertility and assisted reproduction.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, it should be highlighted that it was not made clear in this study whether the control group underwent rigorous testing for SARS-CoV-2 infection [13]. Furthermore, in another study, the same group reported that patients with previous SARS-CoV-2 infection who underwent frozen embryo transfer cycles with oocytes retrieved prior to infection had lower pregnancy rates, notably those who had recovered fewer than 60 days before embryo transfer [33]. More importantly, the clinical outcomes of patients who underwent IVF during the acute period of SARS-CoV-2 infection are mostly described in case reports [17,18].…”
Section: Discussionmentioning
confidence: 78%